Chief Editor’s Voice Vol.6(1) - Jha, Ashok Kumar (Journal of Management, 2023)
The board of editors of JOM, 2023 is pleased to announce the publication of the new volume 6(1) issue of the Journal of Management. The JOM is a peer-reviewed academic research journal registered with the online academic platform NepJOL, TU Central Library, Kirtipur that offers a platform for academicians, professionals and scholars to publish their original research in the field of management, commerce studies, economics and managerial communication.